NEUTRALIZATION OF CIVIL SERVANTS AS STATE APPARATUS IN THE GOVERNMENT SYSTEM OF INDONESIA - Edwar, Ferry; Mohamad, Abdul Basir (SYNTIFIC, 2025)
Background. Civil Servants hold the position of state apparatus responsible for providing services to the public in a professional, honest, fair, and equitable manner in the implementation of state, governmental, and developmental duties. The purpose of this research was to determine the roles and functions of Civil Servants in the Indonesian government, and to examine how they fulfill their roles as State and public servants while maintaining their neutrality concerning political power. Research Methods. This study uses a normative juridical method, legislative and conceptual approaches. The sources of legal materials used include primary, secondary, and tertiary legal materials. Legal materials were collected through library research. The collected legal materials were systematically processed by classifying them based on legislation, theories, and expert opinions, then analyzed qualitatively. Findings. Civil Servants are public officials regulated by governmental norms, responsible for delivering civil services and public goods. They must be sensitive, responsive, cooperative, disciplined, and aware of their responsibilities. To be effective, they must adhere to a code of ethics and maintain neutrality, free from political influence, and interact fairly and honestly. Conclusion. Civil Servants, as part of the state apparatus and public servants, must be capable of performing their duties professionally and responsibly, and remain clean and free from corruption, collusion, and nepotism in delivering services to the public. They must adhere to Government Regulation No. 42 of 2004 concerning the Development of Corps Spirit and Code of Ethics, while maintaining neutrality and freedom from political party influence.